Analysis of Provincial Poverty in Indonesia (Case Study: Before the Covid 19 Pandemic and During the Covid 19 Pandemic) - Sri Nathasya Br Sitepu (Universitas Gorontalo, 2022)
Poverty uses three measurements, namely: the percentage of poor people (P0), the depth index (P1) and the severity index (P2). Poverty in 2018-2019 has decreased where the Covid 19 Pandemic has not yet occurred in Indonesia. After the Covid-19 Pandemic (2020-2021) there was a restriction on population mobility, thereby reducing income and having an impact on poverty. The object of research uses all provinces in Indonesia. Poverty data is sourced from the Central Statistics Agency and the Covid 19 Task Force. The purpose of the study is to compare poverty and the COVID-19 pandemic in every province in Indonesia. This study uses descriptive statistical analysis using data from 2019 and 2020. The results found five provinces with a high rate of COVID-19 cases including: West Java, Central Java, East Java, North Sumatra, and DI. Yogyakarta. The five provinces with the highest COVID-19 cases experienced an increase in poverty during the 2020 COVID-19 pandemic